2002
DOI: 10.1067/mhn.2002.123859
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based medicine in otolaryngology journals

Abstract: Evaluation of levels of evidence in otolaryngology decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 9 publications
2
50
1
4
Order By: Relevance
“…Those results were higher compared to orthopaedic journals (48 % level 4 studies) [2], to plastic surgery journals (40% level 4 studies) [4] and to ophthalmology journals (58% Level 4 studies) [9]. However, other surgical journals as ear, nose and throat (otolaryngology) journals present a percentage similar to JHSE and RICMA (80% Level 4 studies) [10]. The percentage of level 4 papers in JHSA was lower, as compared to the rest of the hand surgery journals investigated, and it was very close to the one published by Obremskey et al [3], who reported a 68.8% of level 4 papers, in a review of 32 articles published in the JHSA from January to June 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Those results were higher compared to orthopaedic journals (48 % level 4 studies) [2], to plastic surgery journals (40% level 4 studies) [4] and to ophthalmology journals (58% Level 4 studies) [9]. However, other surgical journals as ear, nose and throat (otolaryngology) journals present a percentage similar to JHSE and RICMA (80% Level 4 studies) [10]. The percentage of level 4 papers in JHSA was lower, as compared to the rest of the hand surgery journals investigated, and it was very close to the one published by Obremskey et al [3], who reported a 68.8% of level 4 papers, in a review of 32 articles published in the JHSA from January to June 2003.…”
Section: Discussionmentioning
confidence: 99%
“…The initial introduction of EBM was met with concerns that EBM was a form of "cookbook" medicine based on algorithms and a threat to physician autonomy and individualized treatment decisions. 4 However, as noted by Sackett and colleagues, 1 EBM actually incorporates individual clinical expertise with understanding of the best available evidence and patient preference. EBM principles have been incorporated into medical school education now as the first step to establish a lifelong commitment to evidence-based practice.…”
Section: Barriers To Evidence-based Medicinementioning
confidence: 98%
“…A review of articles making clinical recommendations published in otolaryngology journals showed that the LOE was significantly higher in studies making medical treatment recommendations versus surgical treatment recommendations. 4 Articles making medical and surgical treatment recommendations had LOE ranging from 1 to 4, but the overwhelming majority of studies making surgical treatment recommendations used uncontrolled studies (LOE 4) (86% vs 58%). Although there is a focus on developing and publishing studies with higher LOE, it is important for those reading and evaluating studies to understand the difference between LOE and quality.…”
Section: Barriers To Evidence-based Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…¿Cómo determinar con rigor científico qué acciones comportan más beneficios clínicos o sanitarios en comparación con sus daños o inconvenientes? La Medicina Basada en Evidencias (MBE) es una propuesta para responder a estas interrogantes (8).…”
Section: Sr Directorunclassified